Peningkatan Mutu Pembelajaran Yayasan Pendidikan Ibnu Halim - Ari Wibowo Sembiring; Khoirun Nisa; Mela Safitri Situmorang; Sylvi Marsella Diastami; Mulia Ardiansah Harahap (Pusdikra Publishing, 2022)
The relevance of graduate competencies and the needs of the business world and industry is one of Indonesia's educational problems. To be relevant to these needs, a link and match education plan is needed to produce quality output. This study aims to determine and describe how the quality improvement plan at the Ibnu Halim Education Foundation can produce quality and competitive Indonesian human resources. The research method used is descriptive qualitative research. Data were collected using in-depth interviews, participant observation, documentation and field notes. The data analysis technique includes three stages, namely data condensation, data presentation and data verification. The criteria for data validity include credibility with triangulation, dependability, confirmability and transferability. The result of this research is that the planning for improving the quality of SMKN Purwosari has been well planned, systematic, clear and measurable by the principal and the school development team. Planning is made for the next five years starting from 2021 to 2025. It covers aspects of 1) Curriculum and learning, (2) partnerships 3) Bringing in guest teachers, 4) Internships or industrial work practices, 5) Competency certification, 6) Updates competence of educators and education personnel, 7) Teaching factory/teaching industry, 8) Commitment to absorption, 9) Scholarships or official ties, 10) Infrastructure, and 11) Governance